(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2017)
Background: The treatment for MDR-TB characterized by rigorous treatment regimen for long duration, higher incidence of adverse side effects, lower cure rate, and high treatment costs. This could lead to number of psychosocial problems that influence treatment adherence. MDR-TB patients registered under DOTS Plus programme during the period of 2013-2014 in Chennai and Madurai districts, of Tamilnadu were included for this study. Objective: To understand the psychosocial issues facing MDR-TB patients, who are diagnosed and registered for treatment under DOTS plus programme. Methodology: This study used Focus Group Discussions with people with MDR-TB. Focus Group Discussions were focused on physical, psychological, social and economical challenges which MDR-TB patients faced during their treatment. Results: Most of the study participants did not disclose their TB status, even to their family members. The majority of patients were not aware of the diagnosis of MDR-TB and long duration of treatment. Stigma from family, community and health providers has been experienced by the majority of patients. Patients and their families were afraid of losing economic stability which was already precarious owing to the disease. This fear has often generated a great deal of stress. Conclusion: Study finding indicates that there is a significant psychological, social, and financial impact of MDR-TB that has a direct impact on quality of life of MDR-TB patients and their families. There is a need for psychosocial intervention model (strategies) for MDR-TB patients and their caregivers to mitigate the negative effects. SAARC J TUBER LUNG DIS HIV/AIDS, 2017; XIV(1), page: 14-21